Age, composition and tectonic implications of late Ordovician-early Silurian igneous rocks of the Loel Volcanic Belt, NW Laos. Issue 15 (13th October 2019) - Long, Yongzhen; Zhang, Dexian; Huang, Dezhi; Yang, Xiaoyong; Chen, Shanshan; Bayless, Richard C.
ABSTRACT: Volcanic rocks preserved in the Houay kham area, Loei Fold Belt are important components of the giant Paleo-Tethyan igneous belt. These magmatic rocks, previously mapped as Triassic-Jurassic in age, are composed of dacitic tuff, brecciated rhyolite tuff and a small number of dioritic dikes. In this study, LA-ICP-MS zircon U-Pb dating results show that brecciated rhyolite tuff, dacitic tuff, and dioritic dyke samples have ages of 419.8 ± 1.6 Ma, 449.6 ± 2.6 Ma and 417 ± 4.9 Ma. These are the first documented Late Ordovician to Late Silurian volcanic rocks in the Loei Volcanic Belt or in Southeast Asia. Geochemical analyses of these rocks show that all are calc-alkali to high K, formed in a subduction-related, back-arc basin and are intermediate-acid igneous rocks. Dacitic and brecciated rhyolite tuff samples originated from partial melting of maﬁc crust with medium to strong crustal contamination and weak to medium fractional crystallization. Dioritic dyke samples originated from simultaneous partial melting of gabbroic and metasedimentary rocks with weak to no crustal contamination or fractional crystallization. In the early Ordovician the eastern branch of the Rheic ocean opened and the Indochina terrane drifted away from NE Gondwana and subsequently an Ordovician–Silurian Palaeo-Tethyan Ocean opened. GRAPHIC ABSTRACT: